Teachers' Instructional Practices in Small Classes (Alberta Journal of Educational Research, 2003)
Smaller classes have several immediate contextual benefits for teachers, but do they result in changes to instructional practices? Results from a study of 17 small grade 1 classes indicate that teachers used these contextual benefits to support a variety of grouping practices; individualization; active learning; integration of reading, writing, and speaking; and students' personal skill development in a creative and integrated curriculum. Some used an overall program format and adapted instruction for individuals and groups, whereas others designed for children's individual and social development and integrated this in their daily plans. Instructional practices were best described as fluid and holistic, complex, and multitask, and aimed at literacy achievement.